2014
DOI: 10.1080/00405000.2014.948730
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of fabric constructional parameters on surface roughness of wool fabrics

Abstract: Surface roughness properties of wool fabrics are one of the important parameters of clothing quality and hand feeling. This paper presents a comparison between surface roughness characteristics of wool fabrics produced from different constructional parameters such as warp and weft yarn density, weft yarn count, and weave pattern. Roughness values of fabrics were affected by constructional parameters and the effects were related to fabric cover, fabric thickness, and crimps of yarns in fabric structure. A gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This result could be due to the positioning of the yarns within the fabric structure. An increase in yarn density decreased the gaps between the yarn peaks, decreasing surface roughness [39][40][41].…”
Section: Surface Roughness Of Fabricsmentioning
confidence: 99%
“…This result could be due to the positioning of the yarns within the fabric structure. An increase in yarn density decreased the gaps between the yarn peaks, decreasing surface roughness [39][40][41].…”
Section: Surface Roughness Of Fabricsmentioning
confidence: 99%
“…Similar studies have also reported that due to looser structure of fabrics with long yarn float lengths the fabrics in their weave structure, which can be producing a fabric with longer gaps and (higher or lower) amplitudes, leading to increased fabric roughness. 29,30 As shown in Table 6, the one-way ANOVA was presented which indicates that the statistical analysis can successfully be used to describe the surface roughness of the fabrics based on the weave type in the weft direction of the fabric. The F-value is 179.214 (p < 0.000) which implies that the weave type is significant for surface roughness in the weft direction.…”
Section: Effects Of Weave Type On Surface Roughness In the Weft Direc...mentioning
confidence: 99%
“…cover, porosity, thickness and balance of fabric), affect the fabric surface texture and also surface roughness of fabrics. [7][8][9][10][11][12] In tribology, the dimensionless ratio of the friction force (F) between two bodies to the normal force (N) pressing the bodies together is ¼ F/N. 13 Fabric friction, which is defined as the resistance to motion, can be detected when a fabric is rubbed mechanically against itself or tactually between the finger and thumb.…”
mentioning
confidence: 99%